2021
DOI: 10.3390/ijerph18042111
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Assisted Reproduction Technology (ART) and Social Perception of Childbearing Deadline Ages: A Cross-Country Examination of Selected EU Countries

Abstract: The advancement of assisted reproductive technologies (ART) has gained much attention in relation to childbearing postponement. Our study’s purpose was to empirically examine how perceptions of childbearing deadline age vary in association with availability and prevalence of ART across different countries. The present study used data from the 2006 European Social Survey and the 2006 European Society of Human Reproduction and Embryology to examine selected EU countries. A total sample of 17,487 respondents was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…This finding confirms the results from existing studies showing that a longer duration of oocyte storage is related to lower acceptance levels, especially for social indications (Wennberg et al, 2016). Our results suggest that this is due to social objections regarding delayed childbearing (Billari et al, 2011;Kim and Cho, 2021). The moderation of the vignette effect by the normative preference against late motherhood at the participant level underscores the importance of individuals normative orientations for the resulting attitudes.…”
Section: Discussionsupporting
confidence: 90%
“…This finding confirms the results from existing studies showing that a longer duration of oocyte storage is related to lower acceptance levels, especially for social indications (Wennberg et al, 2016). Our results suggest that this is due to social objections regarding delayed childbearing (Billari et al, 2011;Kim and Cho, 2021). The moderation of the vignette effect by the normative preference against late motherhood at the participant level underscores the importance of individuals normative orientations for the resulting attitudes.…”
Section: Discussionsupporting
confidence: 90%
“…The information gained through impersonal and personal interactions can, in this way, also contribute to the broad diffusion of innovative behaviours (Montogomery and Casterline, 1996;Casterline, 2001). This provides a theoretical argument for explaining the documented positive association at the country level between social age deadlines for childbearing and the prevalence of assisted reproductive treatments (Billari et al, 2011;Kim and Cho, 2021).…”
Section: Compositional Effects and Norm Diffusion Processesmentioning
confidence: 99%
“…For instance, religious people are more likely to conform to traditional family values (Philipov and Berghammer, 2007), but those groups tend to shrink as societies become more secularised (Van de Kaa, 1987;Inglehart, 2006;Lesthaeghe, 2010). Previous research has also found that higher-educated respondents are more likely to perceive later age deadlines for childbearing compared to their lower-educated counterparts (Kim and Cho, 2021), so that a country's educational expansion can be an additional driver of the spread of individualistic values (Lesthaeghe, 2010). In addition to extended periods spent in education, labour-market uncertainty and the lack of a stable relationship are circumstantial factors potentially influencing age norms regarding childbearing.…”
Section: Compositional Effects and Norm Diffusion Processesmentioning
confidence: 99%
See 2 more Smart Citations